Parallel Quantum Computation of Vibrational Dynamics - Komarova, Ksenia; Gattuso, Hugo; Levine, R. D.; Remacle, F. (Frontiers in Physics, 2020)
The vibrational dynamics in a linear triatomic molecule is emulated by a quantum information processing device operating in parallel. The quantum device is an ensemble of semiconducting quantum dot dimers addressed and probed by ultrafast laser pulses in the visible frequency range at room temperature. A realistic assessment of the inherent noise due to the inevitable size dispersion of colloidal quantum dots is taken into account and limits the time available for computation. At the short times considered only the electronic states of the quantum dots respond to the excitation. We show how up to 82 = 64 quantum logic variables can be realistically measured and used to process information. This is achieved by addressing the lowest and second excited electronic states of the quantum dots. With a narrower laser bandwidth (= longer pulse) only the lower band of excited states can be coherently addressed enabling 42 = 16 logic variables. Already this is sufficient to emulate both energy transfer between the two oscillators and coherent motions in the vibrating molecule.